Stereotactic Radiosurgery for Classical Trigeminal Neuralgia - Kodrat, Henry; Novirianthy, Rima (BALI MEDICAL JOURNAL; Vol 5 No 1 (2016), 2016)
Trigeminal neuralgia is a debilitating pain syndrome with a distinct symptom mainly excruciating facial pain that tends to come and go unpredictably in sudden shock-like attacks. Medical management remains the primary treatment for classical trigeminal neuralgia. When medical therapy failed, surgery with microvascular decompression can be performed. Radiosurgery can be offered for classical trigeminal neuralgia patients who are not surgical candidate or surgery refusal and they should not in acute pain condition. Radiosurgery is widely used because of good therapeutic result and low complication rate. Weakness of this technique is a latency period, which is time required for pain relief. It usually ranges from 1 to 2 months. This review enlightens the important role of radiosurgery in the treatment of classical trigeminal neuralgia.
Keywords: pain, radiosurgery, trigeminal.